A Shape‐Memory DNA‐Based Hydrogel Exhibiting Two Internal Memories. (24th February 2016) - Hu, Yuwei; Guo, Weiwei; Kahn, Jason S.; Aleman‐Garcia, Miguel Angel; Willner, Itamar
Abstract: The synthesis of a shape‐memory acrylamide–DNA hydrogel that includes two internal memories is introduced. The hydrogel is stabilized, at pH 7.0, by two different pH‐responsive oligonucleotide crosslinking units. At pH 10.0, one of the T‐A⋅T triplex DNA bridging units is dissociated, resulting in the dissociation of the hydrogel into a shapeless quasi‐liquid state that includes the other oligonucleotide bridges as internal memory. Similarly, at pH 5.0, the second type of bridges is separated, through the formation of C‐G⋅C + triplex units to yield the shapeless quasi‐liquid state that includes the other oligonucleotide bridges as internal memory. By reversible pH triggering of the hydrogel between the values 10.0⇔7.0⇔5.0, the two internal memories cycle the material across shaped hydrogel and shapeless quasi‐liquid states. The two memories enable the pH‐dictated formation of two different hydrogel structures.